Clinical practice guidelines for BRCA1 and BRCA2 genetic testing - Pujol, Pascal; Barberis, Massimo; Beer, Philp; Friedman, Eitan; Piulats, Josep M.; Capoluongo, Ettore D.; Garcia Foncillas, Jesus; Ray-Coquard, Isabelle; Penault-Llorca, Frédérique; Foulkes, William D.; Turnbull, Clare; Hanson, Helen; et al. (European journal of cancer (1990), 2021)
BRCA1 and BRCA2 gene pathogenic variants account for most hereditary breast cancer and are increasingly used to determine eligibility for PARP inhibitor (PARPi) therapy of BRCA-related cancer. Because issues of BRCA testing in clinical practice now overlap with both preventive and therapeutic management, updated and comprehensive practice guidelines for BRCA genotyping are needed. The integrative recommendations for BRCA testing presented here aim to (1) identify individuals who may benefit from genetic counselling and risk-reducing strategies; (2) update germline and tumour-testing indications for PARPi-approved therapies; (3) provide testing recommendations for personalised management of early and metastatic breast cancer; and (4) address the issues of rapid process and tumour analysis. An international group of experts, including geneticists, medical and surgical oncologists, pathologists, ethicists and patient representatives, was commissioned by the French Society of Predictive and Personalised Medicine (SFMPP). The group followed a methodology based on specific formal guidelines development, including (1) evaluating the likelihood of BRCAm from a combined systematic review of the literature, risk assessment models and expert quotations, and (2) therapeutic values of BRCAm status for PARPi therapy in BRCA-related cancer and for management of early and advanced breast cancer. These international guidelines may help clinicians comprehensively update and standardise BRCA testing practices. •Provide update clinical recommendations for BRCA testing for preventive purpose.•Offer testing clinical guidelines for personalised management of early and metatstatic breast cancer.•Actualize germline and tumor testing indications for PARPi-approved therapies.•Address the issues of rapid process and tumor analysis.